2013
DOI: 10.1007/s10552-013-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple primary rules on population-based cancer survival

Abstract: Purpose-Different rules for registering multiple primary (MP) cancers are used by cancer registries throughout the world, making international data comparisons difficult. This study evaluates the effect of Surveillance, Epidemiology, and End Results (SEER) and International Association of Cancer Registries (IACR) MP rules on population-based cancer survival estimates.Methods-Data from five US states and six metropolitan area cancer registries participating in the SEER Program were used to estimate age-standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 13 publications
0
55
0
Order By: Relevance
“…18 Weir et al found an incidence of multiple primaries of 19.7% following the SEER guidelines (or 16.9% IACR rules) in colon and 21% (SEER; 19.9% IACR) in patients with lung cancer. 6 Amer et al found similar incidences of multiple primaries in patients with colon cancer; however, they only reported 5.6% multiple primaries in patients with lung cancer. 11 Long-term survival with multiple primaries is variable and is influenced by cancer type and stage at diagnosis.…”
Section: Epidemiology Of Multiple Primariesmentioning
confidence: 92%
See 1 more Smart Citation
“…18 Weir et al found an incidence of multiple primaries of 19.7% following the SEER guidelines (or 16.9% IACR rules) in colon and 21% (SEER; 19.9% IACR) in patients with lung cancer. 6 Amer et al found similar incidences of multiple primaries in patients with colon cancer; however, they only reported 5.6% multiple primaries in patients with lung cancer. 11 Long-term survival with multiple primaries is variable and is influenced by cancer type and stage at diagnosis.…”
Section: Epidemiology Of Multiple Primariesmentioning
confidence: 92%
“…3 In epidemiological studies, the frequency of multiple primaries is reported to be in the range of 2-17%. [4][5][6][7][8] Many factors can influence the reported numbers of multiple primaries, namely the definition that was applied (see below), the follow-up time since the longer patients are followed up after a primary cancer diagnosis, the higher the likelihood that they may develop a second malignancy and importantly also the patient population studied. 9 Today, the situation of patients with multiple primaries is of increasing relevance and importance.…”
Section: Introductionmentioning
confidence: 99%
“…An important but overlooked fact is the multifocality of cancer, with a surprisingly high frequency of multiple lesions of primary origin (with estimates ranging between 3% and 25%) of same or different histological types, with concomitant or subsequent occurrence (synchronous versus metachronous lesions), and with occurrences at proximal versus distant organ sites (7)(8)(9)). An obvious difficulty is distinguishing between truly independent primary lesions and separate lesions that are the result of distant spread with single initiating events.…”
Section: The Clinical Problemmentioning
confidence: 99%
“…The incidence of second primary malignancy varies greatly in different cancer sites, ranging from 2% to 17% 1. Lung cancer is, by far, at the highest risk of developing second primary, accounting for 21% and 19.9% as reported by the Surveillance Epidemiology and End Results (SEER) and the International Association of Cancer Registries (IACR), respectively 2. Here we report the case of a patient who was diagnosed with stage IV non-small cell lung cancer, developed a second primary in his colon after 3 years and remained stable with more than 5 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%